2013
DOI: 10.1093/treephys/tpt050
|View full text |Cite
|
Sign up to set email alerts
|

The evolution and function of vessel and pit characters with respect to cavitation resistance across 10 Prunus species

Abstract: Various structure-function relationships regarding drought-induced cavitation resistance of secondary xylem have been postulated. These hypotheses were tested on wood of 10 Prunus species showing a range in P50 (i.e., the pressure corresponding to 50% loss of hydraulic conductivity) from -3.54 to -6.27 MPa. Hydraulically relevant wood characters were quantified using light and electron microscopy. A phylogenetic tree was constructed to investigate evolutionary correlations using a phylogenetically independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
101
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(117 citation statements)
references
References 53 publications
12
101
1
3
Order By: Relevance
“…This highlights how important the xylem organization is for embolism spreading, since higher VF values increase intervessel connections (Loepfe et al 2007) and, as this favours the spreading of embolisms from vessel to vessel, make the xylem tissue more vulnerable to embolism (Brodersen et al 2013). This correlation between VF values and P 88 observed for Cistus is particularly relevant considering that previous studies within other plant genera did not find any correlation between both traits (Lens et al 2011, Scholz et al 2013, Hajek et al 2014. These contrasting results indicate that the relevance of VF on resistance to embolism can vary largely among genera, being probably linked to differences in the structure of the vascular system (i.e., diffuse-porous or ring-porous trees) and, in some cases, the vessel arrangement, although this seems not to be the case for Cistus since no differences in V G were observed between species.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…This highlights how important the xylem organization is for embolism spreading, since higher VF values increase intervessel connections (Loepfe et al 2007) and, as this favours the spreading of embolisms from vessel to vessel, make the xylem tissue more vulnerable to embolism (Brodersen et al 2013). This correlation between VF values and P 88 observed for Cistus is particularly relevant considering that previous studies within other plant genera did not find any correlation between both traits (Lens et al 2011, Scholz et al 2013, Hajek et al 2014. These contrasting results indicate that the relevance of VF on resistance to embolism can vary largely among genera, being probably linked to differences in the structure of the vascular system (i.e., diffuse-porous or ring-porous trees) and, in some cases, the vessel arrangement, although this seems not to be the case for Cistus since no differences in V G were observed between species.…”
Section: Discussionsupporting
confidence: 55%
“…They showed that a considerable number of species show both low efficiency and low safety, which suggests that the xylem safety-efficiency trade-off may not have contributed to the divergence of all plant species. Although our study does not concern the cause of the differences in resistance to embolism across these Cistus species, the lack of a safetyefficiency trade-off suggests that such differences would be probably due to differences, e.g., at the intervessel pit membrane level (e.g., thickness, Li et al 2016, microstructure or pore diameters, Scholz et al 2013, Tixier et al 2014 or in those traits related to mechanical strength (Lens et al 2011) more than to the vessel sizes. Our results, therefore, do not support the 'rare pits' hypothesis that postulates a link between xylem efficiency and safety in angiosperms, i.e., wider and, therefore, more efficient vessels should be more vulnerable to embolism (Christman et al 2012).…”
Section: Discussionmentioning
confidence: 82%
“…Black nanoparticles in and on pit membranes and lining xylem conduit walls can be seen in TEM images from many previous studies of angiosperm xylem (Wagner et al, 2000;Schmitz et al, 2008;Jansen et al, 2009;Gortan et al, 2011;Lens et al, 2011;Scholz et al, 2013;Capron et al, 2014;Tixier et al, 2014;Li et al, 2016) as well as in ferns (Brodersen et al, 2014). Schmid (1965) and Schmid and Machado (1968) observed that pit membranes in young wood show a low scattering power, in certain instances to the point of almost complete transparency, while older pit membranes become electron dense again.…”
Section: Evidence For Xylem Surfactantsmentioning
confidence: 89%
“…When an embolized vessel is connected by bordered pits to a functional vessel under negative pressure, a pressure difference develops between both sides of the pit membranes. Drought-induced embolism resistance is determined by both qualitative and quantitative pit characteristics (Lens et al, 2013;Scholz et al, 2013). The probability of air entry into a vessel would increase in a stochastic fashion with its pit area (pit quantity).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the pit quantity in vulnerability to cavitation has been proposed as the rare pit hypothesis (Jarbeau et al, 1995;Wheeler et al, 2005;Christman et al, 2009). A strong correlation between cavitation resistance and the average area of pit overlap between vessels was found for .80 species (Wheeler et al, 2005;Hacke et al, 2006;Scholz et al, 2013). However, this correlation may not be valid when considering a relatively narrow range of cavitation resistance, suggesting also the importance of qualitative pit features such as pit membrane thickness (Lens et al, 2011;Scholz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%